Incompatibility studies of Hungarian sweet cherry (Prunus avium L.) cultivars by traditional test crossings - Békefi, Zs. (International Journal of Horticultural Science, 2004)
Cross-incompatibility is a common phenomenon between various sweet cherry (Prunus avium L.) cultivars. Traditionally, choosing cross-compatible cultivar pairs is based on test crossings in the field.There is a lack of information about fertility relations of novel Hungarian sweet cherry cultivars and selections. We have studied cross-incompatibility in 42 sweet cherry cultivar pairs by test-crossings in the field. Out of those, 3 combinations showed incompatibility and 15 pairs were compatible.Test-crossing results proved that with the knowledge of S-allele constitution of Hungarian cultivars incompatible cultivar pairs are recognised in practice reliably. However, we assume that in sterility not only the S-gene system, but other factors (e.g. abnormal development of pollen or flower) also occur, therefore, their examination would be needed.